Magnetic wood with electromagnetic shielding performance and preparation method and application thereof

NiFe2O4 nanoparticles with high purity and uniform particle size were prepared by one-step hydrothermal method, which solved the problem of low shielding efficiency of existing magnetized wood electromagnetic waves, and achieved an electromagnetic shielding efficiency of 25 to 30dB within 8 to 12Hz frequency to meet commercial needs.

CN119603950APending Publication Date: 2025-03-11ZHEJIANG SUNON FURNITURE MFG +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411869135.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing magnetized wood has low electromagnetic wave shielding performance and cannot meet the needs of commercial electromagnetic shielding. It is mainly because the two-step hydrothermal method cannot accurately control the particle size of NiFe2O4 nanoparticles, resulting in low purity and crystallinity of the nanoparticles and uneven distribution.

Method used

NiFe2O4 nanoparticles were prepared by one-step hydrothermal method. The reaction conditions were controlled to obtain nanoparticles with high purity and uniform particle size by dissolving the nickel salt and iron salt in deionized water, adding sodium hydroxide solution to precipitate, and then heating it in a hydrothermal reactor.

Benefits of technology

The electromagnetic shielding performance of magnetic wood is significantly improved, and the shielding efficiency of 25 to 30dB can be achieved within the electromagnetic wave frequency of 8 to 12Hz, meeting the requirements of commercial electromagnetic shielding performance of more than 20dB.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119603950A_ABST
    Figure CN119603950A_ABST
Patent Text Reader

Abstract

The invention relates to magnetic wood with electromagnetic shielding performance and a preparation method and application thereof, and belongs to the technical field of electromagnetic shielding materials. In order to solve the problems that existing magnetized wood is low in electromagnetic wave shielding efficiency and cannot meet the commercial electromagnetic shielding requirement, the invention provides a preparation method of magnetic wood with electromagnetic shielding performance, which comprises the following steps: soaking dry wood slices in an alkaline precursor solution containing nickel hydroxide and ferric hydroxide; and obtaining the magnetic wood with NiFe2O4 nanoparticles uniformly distributed on the surface of the wood by a one-step hydrothermal method. The prepared magnetic wood can achieve the shielding efficiency of 25-30 dB within the electromagnetic wave frequency of 8-12 Hz, and is suitable for electromagnetic shielding of electronic equipment and building decoration with the light requirement. The magnetic wood with the electromagnetic shielding performance is simple in preparation method, low in energy consumption and low in production raw material cost, and has the characteristics of being natural and renewable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding materials, and in particular relates to magnetic wood with electromagnetic shielding performance and a preparation method and application thereof. Background Art

[0002] With the rapid development of mobile communications and electronic devices, electromagnetic radiation and electromagnetic interference have become issues that cannot be ignored. They not only interfere with the normal operation of electronic devices, but also have potential effects on human health. Electromagnetic shielding materials are used to prevent the propagation and diffusion of electromagnetic waves, limit the radiation energy within a safe range, and thus reduce the harm of electromagnetic waves. Common electromagnetic shielding materials include metal shielding materials, conductive polymer materials, and magnetic materials. Although metal shielding materials can effectively reflect electromagnetic radiation, they will increase the weight of the equipment, and the metal manufacturing and processing costs are high; although conductive polymer materials are light, they have low shielding effectiveness and are easy to wear. Magnetic materials such as ferrite have good absorption and attenuation effects on low-frequency electromagnetic radiation, but ferrite materials are relatively brittle and difficult to process. They are prone to breakage and cracks during processing and use, affecting their shielding effect and reliability. In addition, some metals and plastics used in traditional electromagnetic shielding materials are difficult to degrade in the natural environment, and harmful substances such as heavy metal ions and volatile organic compounds can also cause harm to human health and the environment.

[0003] The invention patent application with publication number CN104827536A discloses a method for preparing hydrophobic magnetized wood, in which wood is mixed with a mixed salt solution and magnetic wood is prepared by a two-step hydrothermal method. Although the preparation of electromagnetic shielding materials based on wood is more environmentally friendly and has lower costs, the electromagnetic wave shielding efficiency of the magnetized wood cannot reach more than 20dB. The reason is that the two-step hydrothermal method cannot accurately control the NiFe 2 O 4 The particle size of the nanoparticles, the purity and crystallinity of the obtained nanoparticles are not high, and the nanoparticles are not evenly distributed on the wood, all of which will affect its electromagnetic properties, reduce its shielding effectiveness, and cannot meet the needs of commercial electromagnetic shielding. Summary of the invention

[0004] In order to solve the problem that the existing magnetized wood has low electromagnetic wave shielding efficiency and cannot meet the needs of commercial electromagnetic shielding, the present invention provides a magnetic wood with electromagnetic shielding performance and a preparation method and application thereof.

[0005] The technical solution of the present invention:

[0006] A method for preparing magnetic wood with electromagnetic shielding performance comprises the following steps:

[0007] Step 1: Prepare wood slices, wash and dry them for later use;

[0008] Step 2: dissolving nickel salt and iron salt in deionized water and stirring evenly, adding sodium hydroxide solution to the obtained mixed solution to obtain nickel hydroxide and iron hydroxide precipitates, and washing the obtained precipitates to neutrality;

[0009] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 1 to 8 mol / L with a sodium hydroxide solution to obtain a precursor solution;

[0010] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, heat at a constant temperature of 180-220° C. for 4-6 hours, take out the wood chips, wash and dry them to obtain magnetic wood with electromagnetic shielding properties.

[0011] Furthermore, the wood in step 1 is basswood, balsa or birch.

[0012] Furthermore, the size of the wood slices in step 1 is 20-50 mm×20-50 mm×1-2 mm.

[0013] Furthermore, the cleaning in step 1 is to place the cut wood chips in deionized water for ultrasonic cleaning for 30 to 60 minutes, and the drying is to vacuum dry them at 60 to 100° C. for 24 hours.

[0014] Furthermore, the nickel salt in step 2 is Ni(NO 3 ) 2 6H 2 O; the iron salt is Fe(NO 3 ) 2 9H 2 O; the molar ratio of the nickel salt to the iron salt is 1:2.

[0015] Furthermore, the precursor solution in step three is a mixed solution of iron hydroxide, nickel hydroxide and sodium hydroxide, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide is 1:2:1-12.

[0016] Furthermore, the alkali concentration is 2 mol / L.

[0017] Furthermore, the drying is performed at 60° C. for 24 hours.

[0018] A magnetic wood prepared by a method for preparing magnetic wood with electromagnetic shielding performance, wherein the magnetic wood can achieve a shielding efficiency of 25 to 30 dB within an electromagnetic wave frequency of 8 to 12 Hz.

[0019] The invention discloses an application of magnetic wood with electromagnetic shielding performance in electromagnetic shielding in the fields of electronic equipment and building decoration.

[0020] Beneficial effects of the present invention:

[0021] The present invention adopts a one-step hydrothermal method to prepare NiFe 2 O 4 The nanoparticles have high purity and crystallinity, uniform particle size and can be evenly filled in the pores and groove structure on the wood surface, increasing the surface roughness and significantly improving the electromagnetic shielding performance of magnetic wood. They can achieve a shielding efficiency of 25 to 30 dB within the electromagnetic wave frequency of 8 to 12 Hz, which can meet the requirements of commercial electromagnetic shielding performance of more than 20 dB.

[0022] The invention utilizes the low density and light weight of the wood substrate to prepare magnetic wood suitable for electromagnetic shielding in electronic equipment and architectural decoration fields with light requirements. The invention has a simple preparation method, low energy consumption, low production raw material cost, and is natural and renewable. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a macroscopic picture of the magnetic wood prepared in Example 1;

[0024] Figure 2 From left to right are electron microscope images of natural basswood slices in step 1 of Example 1 and magnetic wood prepared in step 4 at different magnifications;

[0025] Figure 3 The NiFe uniformly distributed on the surface of the magnetic wood prepared in Example 1 2 O 4 Electron micrograph of nanoparticles;

[0026] Figure 4 The XPS (X-ray photoelectron spectroscopy) spectra of the magnetic wood and natural wood prepared in Example 1;

[0027] Figure 5 This is a comparison diagram of the magnetic properties of the magnetic wood prepared in Example 1 and the natural wood;

[0028] Figure 6 This is a comparison chart of the electromagnetic shielding effectiveness of natural wood and the magnetic wood prepared in Example 1, where a is natural wood and b is the magnetic wood prepared in Example 1. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.

[0030] Example 1

[0031] This embodiment provides a method for preparing magnetic wood with electromagnetic shielding performance, comprising the following steps:

[0032] Step 1, cutting basswood chips into the following sizes: 30 mm (longitudinal) × 30 mm (tangential) × 1 mm (radial), ultrasonically cleaning the cut basswood chips in deionized water for 30 min, and then vacuum drying at 100° C. for 24 h to obtain dried basswood chips;

[0033] Step 2: 0.356 g Ni(NO 3 ) 2 6H 2 O and 0.98436 g Fe(NO 3 ) 2 9H 2 O is dissolved in deionized water, stirred evenly to obtain a uniform mixed solution, and then excess sodium hydroxide solution is added to obtain nickel hydroxide and iron hydroxide precipitates and ensure that the precipitation is complete, and the precipitates are washed with deionized water through a centrifuge until they are neutral;

[0034] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 2 mol / L with a sodium hydroxide solution to obtain a precursor solution, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide in the precursor solution is 1:2:6;

[0035] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, and heat at a constant temperature of 200°C for 4 hours. Take out the wood chips and wash them repeatedly with deionized water to remove the residual chemical reagents. Then, place them in a vacuum oven and dry them at 60°C for 24 hours to obtain magnetic wood@NiFe with electromagnetic shielding performance. 2 O 4 Composite materials.

[0036] Figure 1 This is a macroscopic picture of the magnetic wood prepared in this example. It can be clearly observed from the picture that the magnetic wood sample can be attracted by the magnet.

[0037] Figure 2 From left to right, the electron microscope images of the natural basswood slice in step 1 of this example and the magnetic wood prepared in step 4 at different magnifications (from 100um to 2um) are shown. From the left image, it can be observed that there are many pores and groove structures on the surface of the natural wood. The right image shows that after the one-step hydrothermal method in Example 1, wood@NiFe 2 O 4 Composite material, after forming the sample, the pore and groove structure on the surface of the magnetic wood sample was replaced by NiFe 2 O 4 The nanoparticles are filled and contain significant nanoscale spherical protruding particles, which increase its surface roughness.

[0038] Figure 3 The NiFe is evenly distributed on the surface of the magnetic wood prepared in this embodiment. 2 O 4 Electron microscopy image of nanoparticles. As can be seen from the figure, as shown in the red circle, NiFe 2 O 4 The nanoparticles have uniform particle size and are evenly distributed on the wood surface.

[0039] Figure 4 The XPS spectra of the magnetic wood and natural wood prepared in this example show that 3. NiFe 2 O 4 Grown in situ on natural wood.

[0040] The magnetic properties of the magnetic wood prepared in this embodiment were tested. The samples were cut into suitable sizes, and the magnetism of the natural wood and the samples of this patent were tested using a vibrating sample magnetometer (VSM). Figure 5 This is a comparison of the magnetic properties of the magnetic wood and natural wood prepared in this example. By comparison, it is found that natural wood does not have magnetism, while wood@NiFe 2 O 4 The composite material has good magnetic properties.

[0041] The electromagnetic shielding performance of the magnetic wood prepared in this embodiment was tested using a vector network analyzer (VNA); Figure 6 This is a comparison chart of the electromagnetic shielding effectiveness of natural wood and the magnetic wood prepared in this embodiment, a is natural wood, b is the magnetic wood prepared in Example 1. Tests have shown that the magnetic wood prepared by the present invention can achieve a shielding efficiency of 25-30dB within the electromagnetic wave frequency of 8 to 12 Hz, which exceeds the specified commercial electromagnetic shielding performance of 20dB.

[0042] Example 2

[0043] This embodiment provides a method for preparing magnetic wood with electromagnetic shielding performance, comprising the following steps:

[0044] Step 1, cutting basswood chips into the following sizes: 30 mm (longitudinal) × 30 mm (tangential) × 1 mm (radial), ultrasonically cleaning the cut basswood chips in deionized water for 30 min, and then vacuum drying at 100° C. for 24 h to obtain dried basswood chips;

[0045] Step 2: 0.356g Ni(NO 3 ) 2 6H 2 O and 0.98436 g Fe(NO 3 ) 2 9H 2 O is dissolved in deionized water, stirred evenly to obtain a uniform mixed solution, and then excess sodium hydroxide solution is added to obtain nickel hydroxide and iron hydroxide precipitates and ensure that the precipitation is complete, and the precipitates are washed with deionized water through a centrifuge until they are neutral;

[0046] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 1 mol / L with a sodium hydroxide solution to obtain a precursor solution, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide in the precursor solution is 1:2:5;

[0047] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, and heat at a constant temperature of 200°C for 4 hours. Take out the wood chips and wash them repeatedly with deionized water to remove the residual chemical reagents. Then, place them in a vacuum oven and dry them at 60°C for 24 hours to obtain magnetic wood@NiFe with electromagnetic shielding performance. 2 O 4 Composite materials.

[0048] Example 3

[0049] This embodiment provides a method for preparing magnetic wood with electromagnetic shielding performance, comprising the following steps:

[0050] Step 1, cutting basswood chips into the following sizes: 30 mm (longitudinal) × 30 mm (tangential) × 1 mm (radial), ultrasonically cleaning the cut basswood chips in deionized water for 30 min, and then vacuum drying at 100° C. for 24 h to obtain dried basswood chips;

[0051] Step 2: 0.356g Ni(NO 3 ) 2 6H 2 O and 0.98436 g Fe(NO 3 ) 2 9H2 O is dissolved in deionized water, stirred evenly to obtain a uniform mixed solution, and then excess sodium hydroxide solution is added to obtain nickel hydroxide and iron hydroxide precipitates and ensure that the precipitation is complete, and the precipitates are washed with deionized water through a centrifuge until they are neutral;

[0052] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 3 mol / L with a sodium hydroxide solution to obtain a precursor solution, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide in the precursor solution is 1:2:7;

[0053] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, and heat at a constant temperature of 200°C for 4 hours. Take out the wood chips and wash them repeatedly with deionized water to remove the residual chemical reagents. Then, place them in a vacuum oven and dry them at 60°C for 24 hours to obtain magnetic wood@NiFe with electromagnetic shielding performance. 2 O 4 Composite materials.

[0054] Example 4

[0055] This embodiment provides a method for preparing magnetic wood with electromagnetic shielding performance, comprising the following steps:

[0056] Step 1, cutting basswood chips into the following sizes: 30 mm (longitudinal) × 30 mm (tangential) × 1 mm (radial), ultrasonically cleaning the cut basswood chips in deionized water for 30 min, and then vacuum drying at 100° C. for 24 h to obtain dried basswood chips;

[0057] Step 2: 0.356g Ni(NO 3 ) 2 6H 2 O and 0.98436 g Fe(NO 3 ) 2 9H 2 O is dissolved in deionized water, stirred evenly to obtain a uniform mixed solution, and then excess sodium hydroxide solution is added to obtain nickel hydroxide and iron hydroxide precipitates and ensure that the precipitation is complete, and the precipitates are washed with deionized water through a centrifuge until they are neutral;

[0058] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 5 mol / L with a sodium hydroxide solution to obtain a precursor solution, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide in the precursor solution is 1:2:8;

[0059] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, and heat at a constant temperature of 220°C for 4 hours. Take out the wood chips and wash them repeatedly with deionized water to remove the residual chemical reagents, then place them in a vacuum oven and dry them at 60°C for 24 hours to obtain magnetic wood@NiFe with electromagnetic shielding performance. 2 O 4 Composite materials.

[0060] Example 5

[0061] This embodiment provides a method for preparing magnetic wood with electromagnetic shielding performance, comprising the following steps:

[0062] Step 1, cutting basswood chips into the following sizes: 30 mm (longitudinal) × 30 mm (tangential) × 1 mm (radial), ultrasonically cleaning the cut basswood chips in deionized water for 30 min, and then vacuum drying at 100° C. for 24 h to obtain dried basswood chips;

[0063] Step 2: 0.356g Ni(NO 3 ) 2 6H 2 O and 0.98436 g Fe(NO 3 ) 2 9H 2 O is dissolved in deionized water, stirred evenly to obtain a uniform mixed solution, and then excess sodium hydroxide solution is added to obtain nickel hydroxide and iron hydroxide precipitates and ensure that the precipitation is complete, and the precipitates are washed with deionized water through a centrifuge until they are neutral;

[0064] Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 7 mol / L with a sodium hydroxide solution to obtain a precursor solution, wherein the molar ratio of iron hydroxide, nickel hydroxide and sodium hydroxide in the precursor solution is 1:2:10;

[0065] Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, and heat at a constant temperature of 220°C for 6 hours. Take out the wood chips and wash them repeatedly with deionized water to remove the residual chemical reagents, then place them in a vacuum oven and dry them at 60°C for 24 hours to obtain magnetic wood@NiFe with electromagnetic shielding performance. 2 O 4 Composite materials.

Claims

1. A method for preparing magnetic wood with electromagnetic shielding performance, characterized in that: The steps include: Step 1: Prepare wood slices, wash and dry them for later use; Step 2: dissolving nickel salt and iron salt in deionized water and stirring evenly, adding sodium hydroxide solution to the obtained mixed solution to obtain nickel hydroxide and iron hydroxide precipitates, and washing the obtained precipitates to neutrality; Step 3: The precipitate washed to neutrality in step 2 is adjusted to an alkali concentration of 1 to 8 mol / L with a sodium hydroxide solution to obtain a precursor solution; Step 4: Place the dried wood chips obtained in step 1 into the precursor solution obtained in step 3, place the mixed system in a hydrothermal reactor, heat at a constant temperature of 180-220° C. for 4-6 hours, take out the wood chips, wash and dry them to obtain magnetic wood with electromagnetic shielding properties.

2. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 1, characterized in that: The wood in step 1 is basswood, balsa or birch.

3. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 1 or 2, characterized in that: The size of the wood slices in step 1 is 20-50 mm×20-50 mm×1-2 mm.

4. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 3, characterized in that: The cleaning in step 1 is to place the cut wood chips in deionized water for ultrasonic cleaning for 30 to 60 minutes, and the drying is to vacuum dry them at 60 to 100° C. for 24 hours.

5. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 4, characterized in that: In step 2, the nickel salt is Ni(NO3)2·6H2O; the iron salt is Fe(NO3)2·9H2O; and the molar ratio of the nickel salt to the iron salt is 1:

2.

6. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 5, characterized in that: Step 3: The precursor solution is a mixed solution of ferric hydroxide, nickel hydroxide and sodium hydroxide, wherein the molar ratio of ferric hydroxide, nickel hydroxide and sodium hydroxide is 1:2:1-12.

7. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 6, characterized in that: The alkali concentration is 2 mol / L.

8. The method for preparing magnetic wood with electromagnetic shielding performance according to claim 7, characterized in that: The drying step is drying at 60° C. for 24 hours.

9. A magnetic wood prepared by the method for preparing magnetic wood with electromagnetic shielding performance according to any one of claims 1 to 8, characterized in that: The magnetic wood can achieve a shielding efficiency of 25-30 dB within an electromagnetic wave frequency of 8-12 Hz.

10. Use of the magnetic wood with electromagnetic shielding performance as claimed in any one of claims 1 to 8 in electromagnetic shielding in the fields of electronic equipment and architectural decoration.

Citation Information

Patent Citations

  • Preparation method of hydrophobic magnetized wood

    CN104827536A